Incidência de Aedes aegypti e o perfil epidemiológico de arboviroses no distrito de São José da Mata-PB - Teixeira, Edna Maria de Araújo (2018)
The dissipation of several arboviroses established emergency situation in health in Brazil and that implicated in intense mobilization between states and municipal districts to face the circulation viral that if it turned a challenge of great proportions. The man's actions, especially the economical activity, they have been causing environmental alterations that contribute directly to the re-emergence in health in Brazil. It is indispensable to evaluate the decisive factors in the echo-bio-social context, so that combat actions to the vector are accomplished based in the need and local reality. This way, the present work had as objective verifies the correlation among climatic factors, rising of fast index of Aedes aegypti and epidemic profile of arboviroses in the district of São José da Mata-PB in the period of 2016 and 2017. data of LIRAa those two years old were analyzed and accomplished visited in the homes that presented focuses of the vector for application of socioeconomic questionnaire and symptomatological, later the obtained data were compared to the climatic data of the time (available in the program INMET). It was observed that the number of nurseries of Ae. Aegypti was directly proportional to the accumulated rain in the period and the temperature stayed above the 22°C, which would be favorable for the reproduction of the vector.